Morphological Features of Wild Mallard Ducks on Postnatal Growth Based on Functional Analysis of Capture-Recapture Data - Mauro Giammarino; Piero Quatto; Giulia Genoni (International Ornithology, 2018)
Groups of wild juvenile and adult mallard ducks were captured, ringed, measured, while, juvenile ones already ringed, were remeasured on a subsequent recapture between March and September over a period of 7 years, at a site in Piedmont (Italy). Measurements cover both the rates and the pattern of development of 4 morphological features (head-and-bill-length, bill-length, tarsus-length, and weight). Juveniles were examined and their measurements were compared with the asymptotic value obtained from adults’ measures. A functional data analysis growth model was fitted to data and it yielded plausible quantitative estimates. Tarsus appears to reach the asymptote faster than the other morphological features in this population. Finally, a functional principal components analysis was performed to discriminate sex in growing Mallard ducks.
Keywords: Capture-recapture